Inducible knockout of ∆Np63 alters cell polarity and metabolism during pubertal mammary gland development. Issue 6 (17th December 2019) - Kumar, Sushil; Nandi, Ajeya; Mahesh, Aakash; Sinha, Satrajit; Flores, Elsa; Chakrabarti, Rumela
Abstract : The ∆Np63 isoform of the p53‐family transcription factor Trp63 is a key regulator of mammary epithelial stem cells that is involved in breast cancer development. To investigate the role of ∆Np63 at different stages of normal mammary gland development, we generated a ∆Np63‐inducible conditional knockout (cKO) mouse model. We demonstrate that the deletion of ∆Np63 at puberty results in depletion of mammary stem cell‐enriched basal cells, reduces expression of E‐cadherin and β‐catenin, and leads to a closed ductal lumen. RNA‐sequencing analysis reveals reduced expression of oxidative phosphorylation (OXPHOS)‐associated proteins and desmosomal polarity proteins. Functional assays show reduced numbers of mitochondria in the mammary epithelial cells of ΔNp63 cKO compared to wild‐type, supporting the reduced OXPHOS phenotype. These findings identify a novel role for ∆Np63 in cellular metabolism and mammary epithelial cell polarity. Abstract :